H2 Production of As‐Cast Multialloying Mg‐Rich Alloys by Electrochemical Hydrolysis in NaCl Solution. Issue 5 (22nd March 2022) - Bai, Jing; Li, Danting; Cao, Qianhong; Hou, Xiaojiang; Xu, Yunhua
Abstract : To adjust the hydrolysis H2 generation properties of as‐cast Mg–10wt%Ni (Mg10Ni) alloy, intermediate alloys Mg–Ce and Mg–La are introduced to prepare Mg9Ni10Ce and Mg9Ni10La. The H2 generation thermodynamics are investigated based on microstructures, electrochemical polarization properties, and fitted information of hydrolysis curves by Avrami–Erofeev and Arrhenius equations. The results indicate that Ni/La/Ce alloying elements can modify the microstructures of the Mg matrix by forming active phases Mg2 Ni and Mg12 Ce or Mg17 La2, phase boundaries, and α‐Mg solid‐solution. The H2 generation capacities of Mg10Ni, Mg9Ni10Ce, and Mg9Ni10La are 532, 511, and 444 mL g −1 with 0.63, 0.68, and 0.59 conversion yields in 2.5 h at 293 K in NaCl solution. The conversion yields of Mg10Ni, Mg9Ni10La, and Mg9Ni10Ce can be promoted to 0.88, 0.91 and 0.99 at 308 K with 741, 756 and 690 mL g −1 H2, respectively. Due to the high content of eutectic structure and active phase as well as the stronger electrochemical hydrolysis tendency, the modification effect of La is better than Ce. The microstructure–property relationship and thermodynamics built herein can provide an effective strategy to regulate Mg‐based alloys to achieve a high conversion yield and rapid rate by electrochemical hydrolysis H2 generation. Abstract : The multialloying strategy is proven to be an effective strategy to regulate the thermodynamics of hydrolysis H2 generation of Mg‐based alloys by the electrochemical hydrolysis of formed galvanic cells. The modification effect can be optimized by controlling the phase compositions (primary cell type), quantity, and distribution of the active intermediate phases by various alloying elements.